MK1: On optimizing reservoir management for livelihoods - Senaratna Sellamuttu, Sonali (2009)
This project is about livelihoods, and how they can be improved through reservoir management for multiple uses and users.It is about developing strategies for optimizing the benefits of WSI and increasing the ways in which water can be utilized for the benefit of the poor.